Clinical implementation of contrast-enhanced four-dimensional dual-energy computed tomography for target delineation of pancreatic cancer. Issue 1 (October 2018) - Ohira, Shingo; Wada, Kentaro; Hirata, Takero; Kanayama, Naoyuki; Ikawa, Toshiki; Karino, Tsukasa; Nitta, Yuya; Isono, Masaru; Ueda, Yoshihiro; Miyazaki, Masayoshi; Koizumi, Masahiko; Teshima, Teruki
Abstract: Background and purpose: The accurate delineation of pancreatic tumor with respiratory motion is challenging. This study demonstrates the application of contrast-enhanced four-dimensional dual-energy computed tomography (CE-4D-DECT) for tumor delineation and assesses the objective and subjective image quality. Material and methods: Twelve patients underwent CE-4D-DECT, and quantitative spectral analysis was performed on the resulting virtual monochromatic images (VMI) to determine the optimal VMI (O-VMI) with the highest contrast-to-noise ratio (CNR). The objective value of the CNR between pancreatic parenchyma and tumor, and the subjective measurement with five-point scale were compared between O-VMI, standard VMI (S-VMI, 77 keV) and single energy CT (SECT, 120 kVp). Results: The CNR was the highest in the VMI at 60 keV, and the corresponding CNR in the O-VMI (3.4) was significantly higher ( p < 0.05) than that in the S-VMI (2.4) and the SECT (2.7). The overall mean subjective measurements among 4 radiation oncologists were higher for the O-VMI over the S-VMI and SECT with respect to overall image quality (4.0, 3.3 and 3.7, respectively), tumor enhancement (3.4, 2.6 and 3.2, respectively), and vessel delineation (4.2, 3.6 and 4.2, respectively). Conclusions: The O-VMI derived from the CE-4D-DECT demonstrated its superiority over the S-VMI and SECT in depicting pancreatic tumor.